UPAYA ASEAN FRAMEWORK TO MINIMISE THE HARMFUL EFFECTS OF FAKE NEWS DALAM MENANGANI BERITA PALSU PADA PRA-PEMILIHAN PRESIDEN DI INDONESIA TAHUN 2019 - Istya Geubrina Rizky; Adi Rio Arianto; M. Chairil Akbar Setiawan (Sriwijaya Journal of International Relations, 2022)
Nowadays fake news is a new challenge for all countries because of the impact it has. Especially in the Southeast Asia Region with a high level of internet users, it is easy for people to find hoaxes. In order to overcome fake news, ASEAN officials agreed to carry out regional collaboration to eradicate fake news the impact that would be caused through the ASEAN Frameworks to Minimize the Harmful Effects of Fakenenews. Hoaxes are one of the main problems in elections in various countries, one of which is in Indonesia during the 2019 pre-election. This study aims to analyze the efforts made by the Indonesian government based on the ASEAN Frameworks to Minimize the Harmful Effects of Faknenews in dealing with the spread of fake news or hoaxes that increased in the pre-election in 2019. The author uses 3 frameworks of thought in this research, namely Regional Cooperation, The Role of The Government and Hoaxes. This research was conducted using a qualitative descriptive analysis method. Literature study, literature review and interviews were conducted as data collection techniques. The results of the study stated that the efforts of the ASEAN Frameworks to Minimize the Harmful Effects of Fake news in eradicating fake news in the 2019 pre-election in Indonesia through the Communications and Information Technology were carried out by blocking websites that spread hoaxes, using the ITE Law, Artificial Intelligence System (AIS), Fact-Checking Official Site, Digital Literacy for Society, Community Engagement, and Engaging social media platforms.